Career performance trajectories of Olympic swimmers - Allen, S. V.; Hopkins, W. G.; Vandenbogaerde, T. J. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Assessing the progression of a swimmer`s competitive performance against benchmarks is a key element in talent identification and development, but information about changes in performance of elite swimmers during their formative years is needed to inform these benchmarks. Here we report the effects of age on performance and estimates of performance progression required to attain peak performance at the elite level. METHODS: The swimmers were the top 16 in each event of the 2008 Olympics. Their age at the Olympics was 21.5 ± 3.5 y and 23.9 ± 2.9 y for females and males respectively (mean ± SD). We searched the Web for annual best times of each swimmer from their earliest available competitive performance through to 2011 (4285 times in the 13 stroke and distance combinations for each sex, for 391 swimmers, over 9.8 ± 2.9 y). Times were log-transformed for analysis of changes in performance as percentages using a mixed linear model that included an effect for better performance in Olympic years, an effect for the use of newgeneration swimsuits in 2009, and the effect of age on each swimmer`s times modelled as individual quadratic trajectories. The trajectories were used to estimate age of peak performance and progression of performance leading to the peak. RESULTS: Olympic years and swimsuits accounted for additional performance enhancements in all events of 1.2 ± 0.3 % and 1.1 ± 0.5 % respectively (mean ± between-event SD). After adjustment for these effects, the trajectories for females and males predicted peak performance occurring at ages 23.2 ± 2.1 y and 24.7 ± 2.3 y respectively (mean ± SD). Peak performance occurred at later ages for the shorter distances, with a difference of ~3 y between the shortest and longest distances. Both sexes showed similar progressions to peak performance: over ten years 11.6 ± 6.4 %, and over five years 3.0 ± 1.6 %. DISCUSSION: The improvement off their trend that swimmers showed at the Olympics could be due to better preparation and higher motivation for this pinnacle event, but swimsuits probably also contributed in 2008, as they did in 2009. The surprising finding that peak performance occurred a year or two after the Olympics could be due to Olympic selection of athletes who are still seen to be improving. The range in age of peak performance for different distances presumably reflects different maturation of aerobic and anaerobic capacities and should be considered in event selection. The progression over ten years shows too much between-swimmer variability to allow identification of potential Olympic swimmers, but around five years out from an Olympics our progression data should be useful for talent identification.